Case Report: Hypercalcemia, subcutaneous fat necrosis and nephrocalcinosis in neonates who undergo therapeutic hypothermia: a not so rare association, with different onset time - Domenico Umberto De Rose; Domenico Umberto De Rose; Chiara Maddaloni; Guglielmo Salvatori; Francesca Campi; Antonio Gatto; Ludovica Martini; Immacolata Savarese; Iliana Bersani; Graziamaria Ubertini; Francesca Serrao; Simonetta Costa; et al. (Frontiers in Pediatrics)
Subcutaneous fat necrosis (SCFN) in newborns is an uncommon and self-limiting non-infectious panniculitis. It can occur in the first weeks of life in full-term newborns with hypoxic-ischemic encephalopathy who underwent therapeutic hypothermia. Hypercalcemia may develop and has been implicated as the cause of several complications as nephrocalcinosis. Hypercalcemia has been previously reported to appear only after resolution of skin lesions. Herein, we report how hypercalcemia can be evident already at diagnosis of subcutaneous fat necrosis after therapeutic hypothermia and can be associated with an early onset developing nephrocalcinosis. We compare two cases of these uncommon findings and review the recent literature.